If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(x + -1) + -6 = 6x + -2(4 + x) Reorder the terms: 4(-1 + x) + -6 = 6x + -2(4 + x) (-1 * 4 + x * 4) + -6 = 6x + -2(4 + x) (-4 + 4x) + -6 = 6x + -2(4 + x) Reorder the terms: -4 + -6 + 4x = 6x + -2(4 + x) Combine like terms: -4 + -6 = -10 -10 + 4x = 6x + -2(4 + x) -10 + 4x = 6x + (4 * -2 + x * -2) -10 + 4x = 6x + (-8 + -2x) Reorder the terms: -10 + 4x = -8 + 6x + -2x Combine like terms: 6x + -2x = 4x -10 + 4x = -8 + 4x Add '-4x' to each side of the equation. -10 + 4x + -4x = -8 + 4x + -4x Combine like terms: 4x + -4x = 0 -10 + 0 = -8 + 4x + -4x -10 = -8 + 4x + -4x Combine like terms: 4x + -4x = 0 -10 = -8 + 0 -10 = -8 Solving -10 = -8 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 8(2x-6)=5(3x-7) | | f(x)=300x-5x^2+5 | | 3-4(x-3)=3x-12 | | 3(6+6x)=234 | | 8x+5y=1600 | | 30=x+.06x | | f(x)=300x-5x^2-5 | | F(0)=4x^2-9x+8 | | -40-(-53)= | | =300x-5x^2-5 | | 2a^4-5a^3-2a^2+10a-4=0 | | 2(x-7)+x=11 | | 5-x+2x-29=4x-34 | | (6*x)/2-6*5=(6*x)/3 | | 2(10+5x)=50 | | 29-3b+b^2=0 | | 7-6(x-5)=2x-9 | | M-[2-(2-m)]= | | 3x+7=3(x+8) | | a^4+2a^2-63=0 | | 7(1+2x)=161 | | 1-9B^2= | | -3s-10+s^2=0 | | 1000+5000x=12000 | | 5-5x=-4x+2 | | a^3-4a^2-45a=0 | | 6x+3=6(x+2) | | 2.5x=4.8 | | 9-7(x-2)=4x-13 | | Y=(x-5)(x-1) | | log(4x+1)=0 | | 4x=26-4 |